Biological purification of air polluted with volatile organic compounds by using active sludge recirculation - Zigmontienë, Aušra; Baltrënas, Pranas (Journal of Environmental Engineering and Landscape Management, 2004)
Various methods for removal of volatile organic compounds (VOC) from the air are applied in the world. Their selection is determined by the efficiency and costs of the method. Biofiltration is a new technology to control environmental pollutants helping to regulate emissions of VOC with unpleasant odours in to the air and working environment. When VOC are to be removed from large volumes of air, equipment of biological purification charged with active sludge is used. Such an equipment has a rather simple structure and efficiency of to 98–99 %. Active sludge as a biocharge has both a high concentration of microorganisms compared to stationary charges and good sorption features. Sorptive capacity changes when a load to active sludge is changed, and this has a negative impact on biochemical decomposition of organic substances and, at the same time, on purification efficiency. Calculation and evaluation of an optimal working mode of the equipment enable to avoid desorption of VOC in the system or to diminish it to a minimal value. In the biological air‐purification equipment sorption of an organic substance on the surface of active sludge is running at the initial stage. An organic substance is decomposed biologically only in the second stage, and oxygen dissolved in the system (in the charge) is used and VOC desorption from the system is blocked. One of the main parameters determining the biological air‐purification process and its intensity is change of the concentration of oxygen dissolved (CDO) in water phase and maintenance of its minimal value after termination of aeration (when the equipment is out of operation for some time). In operating equipment with a biocharge one more important problem is encountered ‐ the lifetime of the charge and its renewal in the equipment to maintain required concentration of the active sludge. The goal of the investigation is evaluation of purification efficiency of the equipment and the sorptive capacity of active sludge (depending on a load), selection of the working mode, uninterrupted biochemical decomposition of organic substances (based on the concentration of dissolved oxygen) when the charge is in its still state, and investigation of its biooxidating properties when a biofilter works with a biologically active charge and with an inactive charge having only sorptive properties. Oro, užteršto lakiaisiais organiniais junginiais, biologinis valymas, taikant aktyviojo dumblio recirkuliaciją Santrauka. Pasaulyje plačiai taikomi įvairūs ore esančių LOJ valymo metodai. Pasirinkimą lemia metodo efektyvumas ir pigumas. Biofiltracija ‐ tai nauja aplinkos teršalų kontrolės technologija, padedanti reguliuoti nemalonaus kvapo lakiųjų organinių junginių (LOJ) emisijas į atmosferą ir darbo aplinkos ore. Dideliems oro, užteršto lakiaisiais organiniais junginiais, kiekiams valyti taikomi biologinio valymo įrenginiai, kuriuose kaip įkrova naudojamas aktyvusis dumblas. Tokie įrenginiai esti nesudėtingos konstrukcijos, jų efektyvumas – 98–99 %. Aktyviajam dumblui, naudojamam kaip bioįkrova įrenginyje, būdinga ne tik didelė mikroorganizmų koncentracija, palyginti su nuostoviosiomis įkrovomis, bet ir geros sorbcinės savybės. Vienas iš pagrindinių parametrų, lemiančių biologinį oro valymo procesą ir jo intensyvumą, – ištirpusio deguonies koncentracijos (IDK) vandeninėje fazėje kitimas ir palaikoma minimali jos reikšmė nutraukus aeraciją (įrenginiui nedirbant tam tikrą laiko tarpą). Eksploatuojant įrenginius su bioįkrova, susiduriama ir dar su viena svarbia problema – įkrovos ilgaamžiškumu ir būtinumu ją atnaujinti reikiamai aktyviojo dumblo koncentracijai įrenginyje palaikyti. Tyrimų tikslas ‐ įvertinti valymo įrenginių efektyvumą, aktyviojo dumblo sorbcinę talpą (priklausomai nuo apkrovos) ir parinkti veikimo režimą, kad nepertraukiamai vyktų biocheminis organinių medžiagų skaidymas (pagal ištirpusio deguonies koncentraciją), įkrovai esant ramybės būsenos, bei biooksidacinių savybių tyrimai, biofiltrui veikiant su biologiškai aktyvia ir tik sorbcinių savybių (neaktyvia) turinąia įkrova. Reikšminiai žodžiai: organiniai junginiai, biologinis oro valymas, aktyvusis dumblas, sorbcinė apkrova, LOJ desorbcija, ištirpusio deguonies koncentracija. First Published Online: 14 Oct 2010